Illusions of Triumph : An Arab View of the Gulf War - Heikal, Mohamed (London HarperCollins Publishers, 1992)
Mohamed Heikal is one of the Arab world's most distinguished journalists and commentators. This book describes the Gulf War and the events which led up to it from an Arab perspective - a perspective very different from the often simplistic and stereotypical reporting of the Western media.
Include Index
Keywords: Persian Gulf War (1991) -- Politics and government -- Middle East -- Arab countries